Stychomytia w oczach scholiastów. Charakterystyka i analiza komentarzy do wersów 414-420 eurypidesowego "Orestesa" - Czerwińska, Jadwiga; Chiżyńska, Katarzyna (Collectanea Philologica, 2024)
The purpose of this article is to compile and discuss the scholia for a specific form of dialogue used in ancient drama, which is the stichomytia. The paper will use the example of the stichomytia from Euripides’ Orestes to discuss the nature of this type of dialogue and the issues the scholiasts raised in this context. The authors present translations of the scholia and discuss the nature of the scholiasts’ commentaries, many of which are paraphrases of the text of the drama.